Beyond the surface: a narrative inquiry into the transformation of prospective teachers' pedagogical content knowledge for early numeracy - Deane Umboh; Jeane Kalengkongan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study explores how prospective teachers' Pedagogical Content Knowledge (PCK) for early numeracy is articulated and reconstructed across different stages of teacher education. While prior research has examined PCK development, limited attention has been given to how prospective teachers at varying stages conceptualize and integrate numeracy knowledge within practice. Addressing this gap, the study aims to compare narrative representations of PCK among prospective teachers at early, intermediate, and final stages of their preparation. Adopting a qualitative narrative inquiry approach, data were collected from six participants through in-depth interviews and classroom observations within a single semester. Rather than tracking the same individuals over time, the study contrasts developmental perspectives across stages. Data were analyzed using thematic-narrative analysis to identify patterns in how PCK is understood and enacted.The findings reveal three interconnected trajectories: (1) From Abstraction to Awareness, reflecting a shift from procedural to more conceptual understandings of numeracy; (2) Awakening the Need for Concreteness, indicating increasing recognition of the role of representations and manipulatives; and (3) Pedagogical Integration in Action, illustrating emerging alignment between content knowledge and instructional strategies. These trajectories are synthesized into a meta-narrative that highlights the role of reflection, field experiences, and dialogic engagement in shaping PCK. The study contributes to the literature by offering a stage-based narrative perspective on PCK in early numeracy, providing insights for structuring teacher education programs. However, findings are limited to a small sample within a specific institutional context and should be interpreted accordingly. Implications highlight the importance of integrating reflective practice and field-based experiences to support prospective teachers' pedagogical development.